Wildlife Ecosystem Resilience in the Context of Climate Change: A Kootenay Case Study on Stakeholder Perspectives on Conservation Interventions - Davis, Roderick Leigh (2015)
The Kootenay Region of British Columbia is an important landscape connection for wildlife diversity in the Yellowstone to Yukon ecoregional corridor. Significant conservation efforts have provided substantial areas designated to protect wildlife ecosystems in this area. Yet climate change and on-going human development threaten the future resilience of these ecosystems. In light of this complex problem, the goal of this dissertation is to evaluate the effectiveness of current wildlife conservation policy mechanisms, their potential vulnerability in the face of climate change, and the motivation of stakeholders to support policy adaptations. In particular, the research undertakes to understand how community support for adaptation strategies that mitigate climate change impacts on wildlife ecosystems may evolve through direct engagement in conservation assessment and design processes. The thesis therefore addresses the overarching question: “How does stakeholder engagement in an assessment of climate change impacts on wildlife ecosystems influence support for appropriate wildlife habitat and species intervention policies?” The dissertation reviews conservation policies applicable to British Columbia, reviews the efficacy of how those policies are implemented in the Kootenay Region, assesses the potential scope of ecosystem vulnerability to climate change in the region, and evaluates how stakeholder values, beliefs and attitudes motivate support for wildlife conservation and how this is influenced by engaging in a workshop that explores scenarios and impacts of climate change. The efficacy of current conservation policies was evaluated against ecosystem representation, objectives from the Kootenay-Boundary Land Use Plan, the recent ecoregional assessment for the Canadian Rocky Mountains prepared by the Nature Conservancy of Canada, the Mountain Caribou Recovery Plan, conservation of habitat for Grizzly bears, fisher, lynx, wolverine and wolves, and recent conservation proposals. The potential for climate change ...